AB0485 Golimumab's efficacy in patients with very active disease in methotrexate-naÏve rheumatoid arthritis. (23rd January 2014) - Emery, P.; Fleischmann, R.; Hsia, E.C.; Xu, S.; Xu, W.; Baker, D.
Abstract : Objectives: To assess golimumab (GLM) treatment effect in patients with rheumatoid arthritis (RA) naïve to methotrexate (MTX) therapy with severe, active and progressive disease. Methods: The GO-BEFORE trial studied GLM 50mg and 100mg + MTX in MTX-naïve patients. In the overall GO-BEFORE study population, patients exhibited lower disease activity (baseline ACR components and DAS28) than was observed in previous studies of biologic agents in MTX-naive patients 1 . This is a retrospective analysis of GO-BEFORE wk 52 data which compares efficacy outcomes in subsets of RA patients with severe, active disease to the overall study population. 637 MTX-naïve pts were randomized to PBO+MTX (Grp 1), GLM 100mg+PBO (Grp 2), GLM 50mg+MTX (Grp 3), or GLM 100mg+MTX (Grp 4). GLM/PBO received injections q4wks. Pts with 5.1, and CRP ≥3 mg/dL. Treatment effect for each subset and the overall population was defined as the differences between GLM 50mg or 100mg +MTX and MTX-alone in ACR50, DAS28 (CRP) remission, change in HAQ ≥0.25 and total vdHS score ≤0. Differences in the treatment effect between each subset of severe, active and progressive RA and the overall population was examined. Results: Greater proportions of patients achieved the efficacy endpoints in the GLM+MTX groups versus MTX-alone and the difference between the treatment groups (tx effect) was generally larger in the severe, active and progressive subsets compared with the overall population (Table). Conclusions: Overall, treatment effect in the efficacy parameters between GLM 50mg +MTX and GLM 100mg +MTX versus MTX-alone was greater for the severe, active and progressive subsets versus the overall population. References: Emery et al. Arthritis & Rheumatism 2009;60(8):2272-2283. Disclosure of Interest: P. Emery Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, R. Fleischmann Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, E. Hsia Employee of: Janssen Research & Development, LLC, S. Xu Employee of: Janssen Research & Development, LLC, W. Xu Employee of: Janssen Research & Development, LLC, D. Baker Employee of: Janssen Research & Development, LLC